2023
DOI: 10.1155/2023/4151224
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D Levels in Type 2 Diabetes Patients in North China: Seasonality and the Association between Vitamin D Status and Glycosylated Hemoglobin Levels

Abstract: Background and Aims. Previous studies have reported a correlation between vitamin D levels and seasonality in healthy populations. However, there are few studies on the seasonal variation in vitamin D levels and its relationship with glycosylated hemoglobin (HbA1c) in patients with type 2 diabetes mellitus (T2DM). The objective of this study was to investigate seasonal changes in serum 25-hydroxyvitamin D [25(OH)D] levels and the associations between these vitamin D concentrations and HbA1c levels in T2DM pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[ 17 ] Recent Indian and Chinese studies have reported 75% and 64% of VDD among T2DM individuals, respectively. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Recent Indian and Chinese studies have reported 75% and 64% of VDD among T2DM individuals, respectively. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] Wang et al, 2023 reported that women with T2DM exhibited increased susceptibility to VDD, and there was an inverse correlation between vitamin D levels and HbA1c. [ 19 ] In a Brazilian study, the prevalence of hypovitaminosis D in T2DM was correlated with a high BMI, obesity, and HbA1c. [ 24 ] Similarly, a German study reported that VDD was linked with the prevalence of T2DM and severe VDD was significantly associated with increasing FPG levels and HbA1c.…”
Section: Discussionmentioning
confidence: 99%
“…Achieving blood glucose control is one of the goals of diabetes treatment. Serum 25(OH)D 3 levels can be an independent risk factor for increased levels of glycated hemoglobin in T2DM, with women being at a higher risk of vitamin D deficiency ( 7 ). In addition to finding that vitamin D can be a risk factor for glycemic control, it is interesting to note that in patients with T2DM, the combined administration of metformin and vitamin D resulted in better glycemic and glycosylated hemoglobin control compared to metformin alone ( 8 ).…”
Section: Relationship Between Vitamin D Levels and Diabetesmentioning
confidence: 99%